European gas oil markets : price relationships, hedging and efficiency - Long, D (Oxford Institute for Energy Studies, 1991)
The structure of markets is often taken for granted. Companies trade in a commodity market because it exists and do not feel the need to enquire into its origins. But markets are not static entities and, in the case of the oil industry, they are in a constant state of evolution as new trading techniques and new institutions are borrowed or created to satisfy the demands of the wide range of companies that now trade oil. And changes in market structure and performance can have important implications for the trading results of those involved.